(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Describing the current situation of outpatient drug prescriptions at the Department of Obstetrics and Gynecology, Tan Chau Regional General Hospital, An Giang Province in 2019. Subjects and methods: Study of cross-sectional description over 400 oupatient treatment prescriptions stored at the Department of Obstetrics and Gynecology, Tan Chau Regional General Hospital, An Giang Province during from January 1st, 2019 to December 31st, 2019. Results: Comply with the provisions in the prescription; 100% of prescriptions were fully filled out the name, age, sex, diagnosis, cross out the blank, full name and signature of the doctor, the amount of medicine; 100% full patient address; 78.25% written their original names in accordance with regulations; 89.00% recorded sufficient content; 100% indication of the full dose and time of drug usage; 100% full used way. The average number of drugs in 1 prescription was 4.53; 80.75% of drugs were prescribed by the original name; 20.50% of prescriptions had antibiotics; 14.0% of prescriptions had vitamins; 100% of the drugs prescribed were on the essential drug formulary and the hospital formulary. Conclusion: A high proportion of compliance with regulations on prescription was observed. The average number of drugs in 1 prescription was 4.53. Mainly, drugs were prescribed by original name, drugs in the essential drug formulary, the proportion of prescriptions with antibiotics and vitamins was low.